Effects of corn straw-based fermented total mixed rations supplemented with exogenous cellulase on growth performance, digestibility, and rumen fermentation in growing beef cattle - Junzhao Xu; Xiaoni Wang; Huaxin Niu (Animal Bioscience)
Objective This study aimed to assess the impact of corn straw-based unfermented and fermented total mixed rations (TMR) supplemented with exogenous cellulase on the in vitro fermentation characteristics, growth performance, feeding behavior, apparent digestibility, rumen fermentation and digestive enzyme activities of Chinese Simmental bulls. Methods Unfermented (direct spraying of exogenous cellulase onto TMR, TMR) and fermented (exogenous cellulase fermentation for more than 7 d, fermented total mixed rations [FTMR]) TMR were collected, dried, powdered and used as fermentation substrates. The fermentation liquid was ruminal fluid collected from Chinese Simmental bulls. The artificial rumen culture fluid were continuously cultured in vitro for 48 h. Based on the diets they were fed, 24 healthy Chinese Simmental bulls (average weight of 495.93±10.89 kg) were randomly divided into two groups, with 12 bulls in each group, which were fed TMR or FTMR. The study lasted 56 d. Results In in vitro experiments, the neutral detergent fiber (NDF) degradability and total volatile fatty acid, propionate, iso-butyrate, iso-valerate and valerate concentrations were greater in the FTMR group (p<0.05) than in the TMR group. However, the methane production, pH and acetate/propionate (A/P) of the FTMR group tended to be lower (p<0.05) than those of the TMR group. In the in vivo experiments, the average daily gain, eating rate, and feed efficiency of the FTMR groups were greater (p<0.05) than those of the TMR group. Similarly, the NDF degradability of the FTMR group was greater (p<0.05) than that of the TMR group. Compared to those in the TMR group, the concentrations of total volatile fatty acids, iso-butyrate, propionate and butyrate were greater in the FTMR group (p<0.05), and the A/P ratio was lower (p<0.05). Similarly, cellulase, xylanase, and β-glucosidase activities were greater (p<0.05) in the FTMR group than in the TMR group. Conclusion Corn straw-based FTMR supplemented with exogenous cellulase play a vital role in decreasing the structural carbohydrate content of TMR and ruminal methane production in vitro, improving nutrient digestion and absorption, optimizing rumen fermentation, and improving the growth performance of beef cattle.